2014
DOI: 10.4103/0974-2700.125631
|View full text |Cite
|
Sign up to set email alerts
|

Free air on plain film: Do we need a computed tomography too?

Abstract: Context:Standard teaching is that patients with pneumoperitoneum on plain X-ray and clinical signs of abdominal pathology should undergo urgent surgery. It is unknown if abdominal computed tomography (CT) provides additional useful information in this scenario.Aims:The aim of this study is to determine whether or not CT scanning after identification of pneumoperitoneum on plain X-ray changes clinical management or outcomes.Settings and Design:Retrospective study carried out over 4 years at a tertiary care acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It is unclear if the results described herein would pertain to these patients. In a small study involving 25 patients with pneumoperitoneum on plain radiography by Solis et al, peritonitis was indicative of the need for operative intervention 41 . In addition, we excluded patients who did not receive a surgical consult as we believe that these patients were unlikely to have the opportunity for operative intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if the results described herein would pertain to these patients. In a small study involving 25 patients with pneumoperitoneum on plain radiography by Solis et al, peritonitis was indicative of the need for operative intervention 41 . In addition, we excluded patients who did not receive a surgical consult as we believe that these patients were unlikely to have the opportunity for operative intervention.…”
Section: Discussionmentioning
confidence: 99%
“…47 Solis et al 38 showed in a small retrospective study that CT delays surgery in patients with pneumoperitoneum on abdominal radiograph. Thus, given the risk of unnecessary laparotomy and unnecessary delays in surgery where it is required, patients with strong clinical suspicion of GI perforation should ideally have a CT instead of Abdominal X-ray (AXR) as first line investigation (Figure 3).…”
Section: Gastrointestinal Perforationmentioning
confidence: 99%
“…37 It is usually identified as pneumoperitonem on an erect chest and/or abdominal radiograph. 38 Specific signs include Rigler sign, football sign and triangle sign. 31,39 Plain abdominal radiography is not accurate for pneumoperitoneum with studies on specificity ranging from 53% to 89.2%.39-42 False positive results can result in unnecessary laparotomy and needless exposure to general anaesthesia.…”
Section: Gastrointestinal Perforationmentioning
confidence: 99%
“…Plain abdominal radiography have a sensitivity of 53% to 89.2% compared with 86% to 100% when CT is used, but adding the CT will add a delay to the operation room. 12 The combination of a supine or decubitus radiographs with an erect chest film may be the only available modalities in hospitals with limited resources.…”
mentioning
confidence: 99%